Unusual flexibility of mesophase pitch-derived carbon materials: An approach to the synthesis of graphene - Berreda,D; Pérez-Mas,AM; Casco,ME; Rudi,S; Herdes,C; Muller,EA; Blanco,C; Santamaria,R; Silvestre-Albero,J; Rodriguez-Reinoso,F (Carbon, 2017)
Structural flexibility in a petroleum pitch-derived carbon material has been indirectly evaluated using X-ray diffraction (XRD), immersion calorimetry and inelastic neutron scattering (INS) measurements. Exposure of the carbon material to an organic solvent (e.g., n-nonane) gives rise to a large internal rearrangement, associated with a drastic re-ordering of the graphitic microdomains. These structural changes are also associated with a high flexibility of the internal porous network, as observed by inelastic neutron scattering measurements. The internal rearrangement and the structural flexibility could be responsible for the excellent performance of this kind of activated carbons in a wide variety of adsorption processes. Last but not least, the structural characteristics of these carbon materials composed of graphitic microdomains has been used to synthesize graphene “egg-like” flakes following a simple procedure based on exfoliation with organic solvents.